Moyamoya Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
Sixteen children with moyamoya disease and involvement of the posterior cerebral artery are reported from the Departments of Neurophysiology, Neurosurgery, and Radiology, Faculty of Medicine, Kyushu University, Fukuoka, Japan.